Individual stellar haloes of massive galaxies measured to 100 kpc at 0.3 < z < 0.5 using Hyper Suprime-Cam. Issue 3 (15th December 2017) - Huang, Song; Leauthaud, Alexie; Greene, Jenny E; Bundy, Kevin; Lin, Yen-Ting; Tanaka, Masayuki; Miyazaki, Satoshi; Komiyama, Yutaka
Abstract: Massive galaxies display extended light profiles that can reach several hundreds of kiloparsecs. We use data from the Hyper Suprime-Cam (HSC) survey that is simultaneously wide (∼100 deg 2 ) and deep (>28.5 mag arcsec −2 in i band) to study the stellar haloes of a sample of ∼7000 massive galaxies at z  ∼ 0.4. The depth of the HSC data enables us to measure surface mass density profiles to 100 kpc for individual galaxies without stacking. As in previous work, we find that more massive galaxies exhibit more extended outer profiles than smaller galaxies. When this extended light is not properly accounted for (because of shallow imaging and/or inadequate profile modelling), the derived stellar mass function can be significantly underestimated at the high-mass end. Across our sample, the ellipticity of outer light profile increases substantially with radius. We show for the first time that these ellipticity gradients steepen dramatically as a function of galaxy mass, but we detect no mass dependence in outer colour gradients. Our results support the two-phase formation scenario for massive galaxies in which outer envelopes are built up at a later time from a series of merging events. We provide surface mass density profiles in a convenient tabulated format to facilitate comparisons with predictions from numerical simulations of galaxy formation.